Conditional cash transfers in Latin America - Adato, Michelle; Hoddinott, John F. (International Food Policy Research Institute, 2010)
Conditional cash transfer programs (CCTs) have become increasingly popular in low-income countries, particularly in Latin America. CCTs involve cash payments to poor families when they participate in educational, health-related, nutritional, or other services that could help lift them out of poverty. The apparent success of CCTs has led some development specialists to refer to CCTs as "a magic bullet." Conditional Cash Transfers in Latin America evaluates the effectiveness and reliability of CCTs in reducing poverty. The contributors synthesize evidence and analysis from four case studies of Brazil, Honduras, Mexico, and Nicaragua. Using state-of-the-art quantitative and qualitative methods, the studies examine various aspects of CCTs, including the trends in development and political economy that fostered interest in them; their impacts on education, health, nutrition, and food consumption; and how CCT programs affect -- and how their outcomes are affected by -- social relations shaped by gender, culture, and community. Throughout, the authors identify the strengths and weaknesses of CCTs and offer guidelines to those who design them. Successful programs depend on a clear definition of program goals, adapting program design to a particular country's circumstances, effective communication with CCT beneficiaries, high-quality services, and an appreciation of social relations within a given community. This new study is a valuable resource for anyone trying to understand, implement, improve, and build on the success of established conditional cash transfer programs.